Acute Appendicitis as the Initial Clinical Presentation of Primary HIV-1 Infection. (9th January 2018) - Schleimann, Mariane H; Leth, Steffen; Krarup, Astrid R; Mortensen, Jesper; Barstad, Bente; Zaccarin, Matthias; Denton, Paul W; Mohey, Rajesh
Abstract: We report a case of an adolescent who presented at our emergency department with acute abdominal pain. While the initial diagnosis was acute appendicitis, a secondary and coincidental diagnosis of primary HIV-1 infection was made. Concurrent and subsequent clinical and molecular biology findings form the basis of our argument that primary HIV-1 infection was the cause of acute appendicitis in this individual.